Analysis of The Effect of Financial Literacy, Investment Knowledge, Investment Motivation and Perception of Return on Interest Accounting Student Investments - Wardana, Nahdah Ayu; Olda, Yuki; Rena, Rena (Asosiasi Dosen Akuntansi Indonesia, 2023)
This research aims to see how financial literacy, investment knowledge, investment motivation, and return perceptions influence accounting students' investment interest. The aim is to analyze how the influence of Financial Literacy has a significant influence on investment interest, analyze how the influence of Investment Knowledge has a significant influence on investment interest, analyze how the influence of Investment Motivation has a significant influence on investment interest, and to analyze how the influence of Return Perception has a significant influence on investment interest. This research uses quantitative methods. The data collection technique uses a closed questionnaire using a 20 point Likert scale. In accordance with the findings of research conducted on the FE Accounting Student Force at Medan State University, students' ability to invest in the capital market is significantly influenced by finances, motivation and perception of return. The results of this research indicate that the Financial Literacy variable has an effect on accounting students' investment interest, the Investment Knowledge variable has no effect on students' investment interest accounting, the Investment Motivation Variable influences students' investment interest accounting, and the Return Perception Variable influence students' investment interest accountancy.